Implementasi Akuntansi Berbasis Akrual: Ketika Pelaporan Keuangan Pemerintah Daerah Berbenah - Savitri, Rizky Ayu (AKTSAR: Jurnal Akuntansi Syariah, 2018)
The aim of this research is yo understand the impact of the implementation of accrual-based accounting at Hastinapura Provincial Government. This research is a qualitative research with interpretive paradigm and using case study approach. Data collection is done through interviews, document review and observation. The results of this research show that accrual-based accounting implementation at Hastinapura Provincial Government involves the integration of accrual-based accounting practices in the scope of policy setting, human resources development of financial management, information technology system, and also evaluation and control system. The impact of the implementation of accrual-based accounting at Hastinapura Provincial Government was not merely a technical accounting change, but also requires change in work patterns and ways of thinking of financial managers.